A way out : America's ghettos and the legacy of racism - Fiss, Owen M. (Princeton University Press, 2003)
After decades of hand-wringing and well-intentioned efforts to improve inner cities, ghettos remain places of degrading poverty with few jobs, much crime, failing schools, and dilapidated housing. Stepping around fruitless arguments over whether or not ghettos are dysfunctional communities that exacerbate poverty, and beyond modest proposals to ameliorate their problems, one of America's leading experts on civil rights gives us a stunning but commonsensical solution: give residents the means to leave. Inner cities, writes Owen Fiss, are structures of subordination. The only way to end the pover.